Titanium or titanium alloy with hydroxyapatite / talc sheet composite coating on surface and preparation method of titanium or titanium alloy

By using pulse electrodeposition technology to form a hydroxyapatite/talc sheet composite coating on the surface of titanium or titanium alloy, the problem of insufficient coating bond strength and stability in the prior art is solved, and the mechanical properties and biological properties of the coating are improved Compatibility effect.

CN119392329APending Publication Date: 2025-02-07SUZHOU GMP NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411541259.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

In the prior art, the bond strength of the hydroxyapatite coating with a titanium or titanium alloy substrate is poor, the long-term stability and biocompatibility of the coating are insufficient, and the mechanical properties are not ideal.

Method used

Using pulsed electrodeposition technology to form a hydroxyapatite/talc sheet composite coating on the surface of titanium or titanium alloy. The coating is improved by adding oxidizing agent and talc sheet to the electrolyte solution and doping the talc sheet into the hydroxyapatite coating. mechanical properties.

Benefits of technology

The mechanical properties of the hydroxyapatite coating are improved, making it have good fatigue resistance, wear resistance and toughness, while maintaining biocompatibility and reducing preparation costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392329A_ABST
    Figure CN119392329A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of material surface modification, in particular to titanium or titanium alloy with a hydroxyapatite / talc sheet composite coating on the surface and a preparation method thereof.The titanium or titanium alloy is subjected to surface treatment to obtain a first intermediate; carrying out first pulse electrodeposition on the first intermediate in a three-electrode system by taking the first intermediate as a cathode, and depositing a hydroxyapatite coating on the surface in situ to form a second intermediate; an oxidizing agent and talc sheets are added into the electrolyte solution, the electrolyte solution is heated in the stirring state, secondary pulse electrodeposition is conducted on the second intermediate in the three-electrode system, the talc sheets are doped in the hydroxyapatite coating, and therefore the titanium or titanium alloy with the hydroxyapatite / talc sheet composite coating on the surface is obtained. According to the invention, the mechanical property of the coating can be improved on the premise of not reducing the biocompatibility of hydroxyapatite, so that the titanium or titanium alloy with the coating has better fatigue resistance, wear resistance and toughness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of material surface modification, in particular to titanium or titanium alloy with a hydroxyapatite / talc flake composite coating on the surface and a preparation method thereof. Background Art

[0002] Hydroxyapatite (HA) is a bioactive material that is similar to the main inorganic components of human bones and teeth and is widely used in the biomedical field, especially in artificial joints, bone repair and dental implants. Coating hydroxyapatite on the surface of titanium or titanium alloy can enhance its bioactivity, bone bonding ability and corrosion resistance.

[0003] In the prior art, a coating is usually formed on a metal surface by dipping, plasma spraying, electroplating, etc. However, the prior art often has the following problems:

[0004] Poor bonding strength between coating and substrate: The bonding strength between hydroxyapatite coating and metal substrate is usually insufficient, and implants are usually prone to peeling in physiological environments, and the hydroxyapatite coating itself has poor mechanical properties.

[0005] Poor long-term stability of the coating: In the application environment, the coating may degrade or undergo phase changes, affecting its long-term stability.

[0006] Poor biocompatibility: Impurities may be introduced or harmful substances may be produced during the coating preparation process, affecting its biocompatibility.

[0007] The microstructure of the coating is not ideal: the ideal coating should have porosity and appropriate surface roughness to promote cell attachment and growth, but this is difficult to accurately control in the actual preparation process.

[0008] Production cost and efficiency: Some preparation methods such as plasma spraying are costly and have a long production cycle, which is not conducive to large-scale production.

[0009] In response to these problems, researchers are constantly exploring new preparation methods and coating materials in order to improve the performance of hydroxyapatite coatings and reduce their preparation costs. Summary of the invention

[0010] In order to solve the technical problem that the mechanical properties of the hydroxyapatite coating on the metal surface are poor, a titanium or titanium alloy having a hydroxyapatite / talc composite coating on the surface and a preparation method thereof are provided. The preparation process of the invention is simple, no toxic or harmful solvent is used, and the talc is introduced in the synthesis process to form a hydroxyapatite / talc composite coating on the surface of the titanium or titanium alloy, and the talc itself has a certain biocompatibility, and the mechanical properties of the coating can be improved without reducing the biocompatibility of hydroxyapatite, so that the titanium or titanium alloy having the coating of the invention has good fatigue resistance, wear resistance and toughness.

[0011] In order to achieve the above objectives, the present invention is implemented by the following technical solutions:

[0012] A method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface comprises the following steps:

[0013] S1, performing surface treatment on titanium or titanium alloy to increase surface roughness so as to increase the adhesion between the subsequent coating and the substrate, thereby obtaining a first intermediate;

[0014] S2, performing a first pulse electrodeposition on the first intermediate in a three-electrode system using the first intermediate as a cathode, and in-situ depositing a hydroxyapatite coating on the surface of the first intermediate, thereby forming a second intermediate;

[0015] The three-electrode system includes the cathode, a counter electrode, a reference electrode, and an electrolyte solution;

[0016] The electrolyte solution includes raw materials for forming hydroxyapatite;

[0017] S3. Add an oxidant and talc to the electrolyte solution, keep the initial electrolyte concentration of the cathode constant under stirring, and keep the flakes suspended in the electrolyte, heat the electrolyte solution to no more than 80°C, perform a second pulse electrodeposition on the second intermediate in the three-electrode system, and dope talc into the hydroxyapatite coating, thereby obtaining titanium or titanium alloy with a hydroxyapatite / talc composite coating on the surface.

[0018] Furthermore, the electrolyte solution includes: Ca(NO3)2·4H2O, NH4H2PO4, NaNO3 and water, and the pH value of the electrolyte solution is 3-5, preferably the pH value of the electrolyte solution is 4.1-4.3;

[0019] The molar concentration of Ca(NO3)2·4H2O is 0.04M-0.042M, the molar concentration of NH4H2PO4 is 0.022M-0.028M, and the molar concentration of NaNO3 is 0.12M-0.18M.

[0020] Furthermore, the oxidant is hydrogen peroxide, the molar concentration of the hydrogen peroxide is 0.3 M, and the amount of hydrogen peroxide added is 1-5% of the volume of the electrolyte solution. The addition of H2O2 can maintain the electrolyte concentration on the cathode surface, reduce hydrogen evolution and improve the bonding strength between the coating and the substrate.

[0021] Furthermore, the talc tablet has a diameter of 200-1000 μm, a sheet thickness of 1-30 nm, and a purity of at least 90 wt %;

[0022] The amount of the talc tablet added to the electrolyte solution is in the range of 5 g / L-100 g / L, preferably in the range of 10 g / L-80 g / L.

[0023] Furthermore, the process parameters of the first pulse electrodeposition and the second pulse electrodeposition are: applying potential at a frequency of 2 Hz in a pulse constant potential mode, and treating at -5 V for 0.5-3 h. The coating film obtained under this condition is denser and more uniform.

[0024] Furthermore, the electrolyte solution is heated to a temperature of 60-70°C.

[0025] Furthermore, the titanium or titanium alloy is medical titanium or titanium alloy; the surface treatment process is: firstly, the titanium or titanium alloy is wet-grinded with silicon carbide sandpaper to a surface roughness of 1200 mesh, ultrasonically cleaned in acetone for 10 minutes, then rinsed with alcohol solution and / or water, and then immersed in a hydrofluoric acid solution for 1-5 minutes, wherein the mass fraction of the hydrofluoric acid solution is 2%-5%, which can increase the bonding force between the coating and the substrate in turn.

[0026] Furthermore, the counter electrode is made of a graphite rod, and the reference electrode is a saturated calomel electrode (SCE).

[0027] Another aspect of the present invention provides titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface, which is prepared by the above-mentioned preparation method.

[0028] Beneficial technical effects:

[0029] The electrodeposition process is carried out by the action of the current flowing between the working electrode (i.e., the cathode) and the counter electrode, both of which are immersed in an electrolyte solution containing an in-situ hydroxyapatite coating, and then a second electrodeposition is carried out, during which the second phase talc flakes are suspended in the electrolyte solution by stirring, thereby allowing the talc flakes to be incorporated into the in-situ formed hydroxyapatite coating; the electrodeposition forms a nanostructured coating, and the nanostructured talc flakes can improve the mechanical properties of the hydroxyapatite coating; the present invention incorporates talc flakes into the hydroxyapatite coating film in different amounts, and further improves the mechanical properties of the coating without reducing the biocompatibility of hydroxyapatite, so that the titanium or titanium alloy having the coating of the present invention has better fatigue resistance, wear resistance and toughness; pulse electrochemical deposition has the advantages of low cost and easy synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 The SEM images of the surface morphology and cross-sectional thickness of the hydroxyapatite coating obtained after S2 in Example 1; wherein (a) is a surface morphology image, and (b) is a cross-sectional thickness image;

[0031] Figure 2 This is a SEM image of the surface morphology of the hydroxyapatite / talc flake composite coating obtained through all the steps in Example 1;

[0032] Figure 3 The wear track length of each material was tested on a ball-plate tribometer under a normal load of 2 N, a speed of 2 mm / s, and a linear wear track of 2 mm;

[0033] Figure 4 This is a friction coefficient curve of each material under a normal load of 2N, a speed of 2mm / s and a linear wear track of 2mm. The ordinate friction coefficient represents the friction coefficient. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present invention will be described clearly and completely below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0035] Unless otherwise specifically stated, the numerical value set forth in these embodiments does not limit the scope of the present invention. The technology and method known to those of ordinary skill in the relevant art may not be discussed in detail, but in appropriate cases, the technology and method should be considered as a part of the specification. In all examples shown and discussed here, any specific value should be interpreted as being merely exemplary, rather than as a limitation. Therefore, other examples of exemplary embodiments may have different values.

[0036] In addition, it should be noted that the use of terms such as "first" and "second" to limit intermediates is only to facilitate the distinction between the products of each reaction step. Unless otherwise stated, the above terms have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.

[0037] The experimental methods in the following examples without specifying specific conditions are usually measured in accordance with national standards; if there is no corresponding national standard, the method is carried out in accordance with the general standard requirements or general methods.

[0038] The titanium sample used in the following case is 10 mm in diameter and 1 mm in thickness. The chemical composition of the titanium sample (grade 2) specified by the supplier (TiBrasil) is: N (0.01 wt%), C (0.01 wt%), H (0.0023 wt%), Fe (0.07 wt%), O (0.14 wt%), Ti (0.7677 wt%). Of course, titanium alloys of other compositions can also be used in some embodiments.

[0039] Example 1

[0040] A method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface comprises the following steps:

[0041] S1. Surface treatment of the titanium sample: wet-grind the sample to 1200 mesh with SiC sandpaper, ultrasonicate in acetone for 10 minutes, rinse with methanol and distilled water, and then immerse the sample in a 4wt% hydrofluoric acid solution for 2 minutes. The above treatment can increase the surface roughness, which is convenient for increasing the adhesion between the subsequent coating and the substrate, thereby obtaining the first intermediate;

[0042] S2, using the first intermediate as a cathode, a graphite rod as a counter electrode, and a saturated calomel electrode as a reference electrode, immersing each electrode in an electrolyte solution, wherein the electrolyte solution includes: 0.042M Ca(NO3)2·4H2O, 0.025M NH4H2PO4 and 0.15M NaNO3, and the pH value of the electrolyte solution is 4.19;

[0043] The first intermediate is subjected to a first pulse electrodeposition in a three-electrode system. The process parameters of the pulse electrodeposition are: applying a potential at a frequency of 2 Hz in a pulse constant potential mode, treating at -5 V for 1 hour, and in-situ depositing a hydroxyapatite coating (abbreviated as HA coating) on ​​the surface of the first intermediate to form a second intermediate. The second intermediate product is named HA.

[0044] The HA coating obtained through the above steps was observed by SEM, and the SEM images of its surface morphology and cross-sectional thickness are shown in Figure 1 As shown by Figure 1 It can be seen that the surface HA coating is denser and thinner, and the thickness of the HA coating is about 34.7 ± 0.03 μm;

[0045] S3. Add hydrogen peroxide (molar concentration of 0.3M) and talc to the electrolyte solution, wherein the amount of hydrogen peroxide added is 2% of the volume of the electrolyte solution, and the amount of talc added to the electrolyte solution is 10 g / L. Heat the electrolyte solution to 65°C under stirring, and perform a second pulse electrodeposition on the second intermediate in the three-electrode system. The process parameters of the pulse electrodeposition are: apply a potential at a frequency of 2 Hz in a pulse constant potential mode, treat at -5 V for 1 h, and dope talc into the hydroxyapatite coating to obtain a titanium sample with a hydroxyapatite / talc composite coating on the surface.

[0046] The final product of this case is named T10.

[0047] The SEM surface morphology of T10 obtained after all the steps was observed, and the results were as follows: Figure 2 As shown by Figure 2 Calcium phase crystals and talc flakes are visible.

[0048] Example 2

[0049] The preparation method of the titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface of this case is the same as that in Example 1, except that the amount of talc flakes added to the electrolyte solution in S3 is 40 g / L.

[0050] The final product of this case is named T40.

[0051] Example 3

[0052] The preparation method of the titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface of this case is the same as that in Example 1, except that the amount of talc flakes added to the electrolyte solution in S3 is 80 g / L.

[0053] The final product of this case is named T80.

[0054] Test Case

[0055] Wear tests were performed on bare Ti, HA, T10, T40, and T80. The wear track length and friction coefficient of each material were tested on a ball-plate tribometer under a normal load of 2N, a speed of 2mm / s, and a linear wear track of 2mm. The results are shown in Figure 3 and Figure 4 , and Table 1.

[0056] Table 1 Wear track length of each material

[0057] sample Wear track length (μm) Ti 1001 HA 439 T10 303 T40 437 T80 536

[0058] From Table 1, Figure 3 and Figure 4 It can be seen that despite the higher friction coefficient of the HA coating, the wear track width is much lower than that observed for bare titanium (a reduction of about 56% in the wear track width was observed, see Table 1), which indicates that the wear resistance imparted by the HA coating is increased. The increase in the friction coefficient of the HA coating may be related to the difference in the surface treatment of the material, or it may be an inherent property of the HA coating; at the same time, the lower wear width is related to the hardness of HA, which is higher than Ti. The increase in the friction coefficient is attributed to the presence of the HA phase in the coating, which increases the hardness of the composite material.

[0059] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface, characterized in that: The steps include: S1. Surface treatment is performed on titanium or titanium alloy to increase surface roughness to obtain a first intermediate; S2, performing a first pulse electrodeposition on the first intermediate in a three-electrode system using the first intermediate as a cathode, and in-situ depositing a hydroxyapatite coating on the surface of the first intermediate, thereby forming a second intermediate; The three-electrode system includes the cathode, a counter electrode, a reference electrode, and an electrolyte solution; The electrolyte solution includes raw materials for forming hydroxyapatite; S3. Add an oxidant and talc to the electrolyte solution, heat the electrolyte solution to no more than 80° C. under stirring, perform a second pulse electrodeposition on the second intermediate in the three-electrode system, and dope talc into the hydroxyapatite coating, thereby obtaining titanium or titanium alloy having a hydroxyapatite / talc composite coating on the surface.

2. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to claim 1, characterized in that: The electrolyte solution includes: Ca(NO3)2·4H2O, NH4H2PO4, NaNO3 and water, and the pH value of the electrolyte solution is 3-5; The molar concentration of Ca(NO3)2·4H2O is 0.04M-0.042M, the molar concentration of NH4H2PO4 is 0.022M-0.028M, and the molar concentration of NaNO3 is 0.12M-0.18M.

3. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to claim 2, characterized in that: The oxidant is hydrogen peroxide, the molar concentration of the hydrogen peroxide is 0.3M, and the amount of hydrogen peroxide added is 1-5% of the volume of the electrolyte solution.

4. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to claim 2, characterized in that: The talc tablet has a diameter of 200-1000 μm, a sheet thickness of 1-30 nm, and a purity of at least 90 wt %; The amount of the talc tablet added to the electrolyte solution is in the range of 5 g / L-100 g / L.

5. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to any one of claims 1 to 4, characterized in that: The process parameters of the first pulse electrodeposition and the second pulse electrodeposition are: applying potential at a frequency of 2 Hz in a pulse constant potential mode and treating at -5 V for 0.5-3 h.

6. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to any one of claims 1 to 4, characterized in that: The electrolyte solution is heated to a temperature of 60-70°C.

7. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to any one of claims 1 to 4, characterized in that: The titanium or titanium alloy is medical titanium or titanium alloy; The surface treatment process is: firstly, the titanium or titanium alloy is wet-grinded with silicon carbide sandpaper until the surface roughness is 1200 mesh, ultrasonically cleaned in acetone for 10 minutes, then rinsed with alcohol solution and / or water, and then immersed in hydrofluoric acid solution for 1-5 minutes, wherein the mass fraction of the hydrofluoric acid solution is 2%-5%.

8. The method for preparing titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on the surface according to any one of claims 1 to 4, characterized in that: The counter electrode is made of a graphite rod, and the reference electrode is a saturated calomel electrode.

9. Titanium or titanium alloy having a hydroxyapatite / talc flake composite coating on its surface obtained by the preparation method according to any one of claims 1 to 8.